Asymmetrical Ladder‐Type Donor‐Induced Polar Small Molecule Acceptor to Promote Fill Factors Approaching 77% for High‐Performance Nonfullerene Polymer Solar Cells. Issue 26 (15th May 2018) - Gao, Wei; Zhang, Miao; Liu, Tao; Ming, Ruijie; An, Qiaoshi; Wu, Kailong; Xie, Dongjun; Luo, Zhenghui; Zhong, Cheng; Liu, Feng; Zhang, Fujun; Yan, He; et al.
Abstract: In this work, an effectual strategy of constructing polar small molecule acceptors (SMAs) to promote fill factor (FF) of nonfullerene polymer solar cells (PSCs) is first reported. Three asymmetrical SMAs ofIDT6CN, IDT6CN‐Th, andIDT6CN‐M, which own large dipole moments, are designed and synthesized. The PSCs based on three polar SMAs exhibit apparently higher FFs compared with their symmetrical analogues. The asymmetrical design strategy accompanied with side chain and end group engineering makesIDT6CN‐Th ‐ andIDT6CN‐M ‐based nonfullerene PSCs achieve high power conversion efficiency with FFs approaching 77%. Abstract : The asymmetrical acceptors IDT6CN‐Th and IDT6CN‐M with a large dipole moment outside the molecular backbone show strong π–π stacking in the out‐of‐plane direction. Polymer solar cells based on IDT6CN‐Th and IDT6CN‐M achieve high efficiencies of 10.41% and 11.20% with fill factors (FFs) of 76.72% and 76.83%, respectively, indicating that constructing polar small‐molecule acceptors to enhance the FF is an effective strategy.